Effect of internal helical-rib roughness on mixed convection flow and heat transfer in heated horizontal pipe flow of supercritical water. (March 2019) - Li, Zhouhang; Yao, Yecheng; Wang, Qinggong; Cai, Jingyong; Wu, Yuxin; Wang, Hua
Highlights: Internal helical-rib roughness inhibited the buoyancy effect on heat transfer. Different vortex patterns were identified during the development of secondary flow. Helical ribs aggravated heat transfer inhomogeneity when buoyancy effect was weak. Rib-roughened pipe was preferable when multiple vortexes emerged at Gr q / Gr th  > 200. Internally helical ribs were more effective in vertical flow than in horizontal flow. Abstract: Horizontal flow of supercritical fluids is very common in industrial facilities involving heat transfer. The serious inhomogeneity in the thermal field remains as one of the major concerns need to be addressed in horizontal supercritical flow. This work aims to evaluate the effectiveness of internal helical-rib roughness in improving heat transfer of horizontal supercritical flow. A well-validated, three-dimensional numerical model was employed to solve the turbulent mixed convection. Results show that helical ribs easily inhibited buoyancy effect in horizontal flow. Under condition of weak buoyancy influence, helical ribs hardly improved local or integral heat transfer as a result of barely modified flow field. In heavily buoyancy-affecting mixed convection, strong interaction between natural convection and rib-induced swirl flow was observed. The flow field continued evolving along the flow direction, which resulted in a more uniform thermal field and significant improvement in heat transfer. Variation trend of the location where heat transfer was the worst was identified. Finally, it was concluded that though internal helical-rib roughness is less effective in horizontal flow than in upward flow, it can still significantly relieve the serious thermal inhomogeneity and heat transfer deterioration in horizontal smooth pipes at Gr q / Gr th  > 200.